Chronic Ethanol Consumption Induces Osteopenia via Activation of Osteoblast Necroptosis - Man Guo (Hindawi Limited, 2021)
Chronic high-dose alcohol consumption impairs bone remodeling, reduces bone mass, and increases the risk of osteoporosis and bone fracture. However, the mechanisms underlying alcohol-induced osteoporosis are yet to be elucidated. In this study, we showed that excess intake of ethyl alcohol (EtOH) resulted in osteopenia and osteoblast necroptosis in mice that led to necrotic lesions and reduced osteogenic differentiation in bone marrow mesenchymal stem cells (BMMSCs). We found that EtOH treatment led to the activation of the RIPK1/RIPK3/MLKL signaling, resulting in increased osteoblast necroptosis and decreased osteogenic differentiation and bone formation both in vivo and in vitro. We further discovered that excessive EtOH treatment-induced osteoblast necroptosis might partly depend on reactive oxygen species (ROS) generation; concomitantly, ROS contributed to necroptosis of osteoblasts through a positive feedback loop involving RIPK1/RIPK3. In addition, blocking of the RIPK1/RIPK3/MLKL signaling by necrostatin-1 (Nec-1), a key inhibitor of RIPK1 kinase in the necroptosis pathway, or antioxidant N-acetylcysteine (NAC), an inhibitor of ROS, could decrease the activation of osteoblast necroptosis and ameliorate alcohol-induced osteopenia both in vivo and in vitro. Collectively, we demonstrated that chronic high-dose alcohol consumption induced osteopenia via osteoblast necroptosis and revealed that RIPK1 kinase may be a therapeutic target for alcohol-induced osteopenia.